2012
DOI: 10.1007/s10593-012-0984-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl thioimidates as versatile building blocks for organic synthesis

Abstract: This review discusses the synthesis and application of glycosyl thioimidates in chemical glycosylation and oligosaccharide assembly. Although glycosyl thioimidates include a broad range of compounds, the discussion herein centers on S-benzothiazolyl (SBaz), S-benzoxazolyl (SBox), S-thiazolinyl (STaz), and S-benzimidazolyl (SBiz) glycosides. These heterocyclic moieties have recently emerged as excellent anomeric leaving groups that express unique characteristics for highly diastereoselective glycosylation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…This derivative was first introduced for glycosylation by Mukaiyama et al . In 2011, Hasty and Demchenko introduced another variant of thioglycoside donor, S‐benzimidazolyl (SBiz) glycosides, 85 (Figure ), suitable for extensive oligosaccharide synthesis …”
Section: Glycosylationsmentioning
confidence: 99%
“…This derivative was first introduced for glycosylation by Mukaiyama et al . In 2011, Hasty and Demchenko introduced another variant of thioglycoside donor, S‐benzimidazolyl (SBiz) glycosides, 85 (Figure ), suitable for extensive oligosaccharide synthesis …”
Section: Glycosylationsmentioning
confidence: 99%
“…Over the last decade, we have been interested in syntheses and applications of various glycosyl thioimidates as new, versatile building blocks for chemical glycosylation and expeditious oligosaccharide synthesis. 32 S-Benzoxazolyl (SBox), 33 S-thiazolinyl (STaz), 34 O-methyl phenylcarbamothioate (SNea), 35 and S-benzimidazolyl (SBiz) 36 are all commonly activated with AgOTf. This activation pathway often gives superior yields and stereoselectivity, compared against those achieved with other activators.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, the authors demonstrated that benzoxazolyl 1-thio-β-D-glucopyranoside (GlcSBox) and benzimidazolyl 1-thio-β-D-glucopyranoside (GlcSBiz) hydrolyses were catalysed by remote activation of the C-S bond through protonation of the ring nitrogen in the aglycone. Such remote activation was also described in the case of Araf51 [15], which was able to use similar arabinofuranosyl thioimidates as glycosyl donors in thioglycoligation reaction [29][30][31][32][33][34][35]. In the context of chemoenzymatic synthesis of glycosides, these substrates are attractive because of their high stability towards chemical hydrolysis in aqueous solutions, as well as efficient leaving group ability [15].…”
Section: Introductionmentioning
confidence: 89%